Fabrication of CIGS thin films by using spray pyrolysis and post-selenization - Kim, Seong Yeon; Kim, JunHo (Journal of the Korean Physical Society, 2012)
We fabricated Cu(In 1− x Ga x )Se 2 ( x : 0 ∼ 0.4) thin films by using ultrasonic spray pyrolysis and post-selenization. First, we made Cu(In 1− x Ga x )S 2 ( x : 0 ∼ 0.4) films by ultrasonic spray pyrolysis under an air environment. Then, we converted as-sprayed Cu(In 1− x Ga x )S 2 (CIGS) films to Cu-(In 1− x Ga x )Se 2 (CIGSe) films through post-selenization. For all Ga fractions, the sprayed CIGS films were well recrystallized into poly-crystalline CIGSe films with a dominant (112) texture, which was confirmed by X-ray diffraction, Raman spectroscopy and energy dispersive X-ray analyses. This result indicates that CIGSe films with any amount of Ga substitution can be made by converting sprayed CIGS to CIGSe with post-selenization.